Pengaruh Pekerjaan, Stres, Obesitas, dan Siklus Menstruasi dengan Kejadian Infertilitas pada Wanita - Nani Yuliarfani; Nina Nina (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Infertile events have a big impact on family life because in addition to causing medical problems, infertility can also cause emotional problems psychologically, emotionally to married couples, even not infrequently can affect career and personal life. The purpose of this study was to find out the influence of employment status, stress, obesity, and menstrual cycle with the incidence of infertility in women. The method used in this research is a quantitative approach that uses cross-setional design. The sample was used by 104 respondents. The analytical methods used are Chi Square and Regression Logistics. The results found that there was an influence on employment status (Pvalue 0.000), stress (pvalue 0.002), obesity (pvalue 0.008), and menstrual cycle (pvalue 0.006) with the incidence of infertility in women. The study's work status, stress, obesity and menstrual cycle together (simultaneously) had a significant influence on the incidence of infertility. It is expected that women of childbearing age couples to reduce their work so as not to experience stress that affects irregular menstrual cycles, can lose weight by regulating their diet or diet as needed and providing counseling about infertile so that women of childbearing age partners understand better.Keywords: Infertility, menstruation, obesity, stress, work